The father of library / Nadia Fazira Nor Amir and Nur Sarah Syafiqah Ismail - Nor Amir, Nadia Fazira; Ismail, Nur Sarah Syafiqah (Faculty of Information Management, 2015)
Based on Dictionary reference.com (2007) hero is a person who is admired for their courage, outstanding achievements or noble qualities. Typically people will glorify a person as their heroes based on physical, bravery and the strength of that person such as Superman, Captain America and any other superheroes that famous nowadays. Hero is the person who people will look up, respect and admire. In library world, a library classification or also known as bibliographic classification is a system according to which library materials or information resources are arranged on library shelves, typically according to subject and allocating a call number.